An Ancient Egyptian Wig: Construction and Reconstruction - Joann Fletcher; Filippo Salamone (Internet Archaeology, 2016)
A study of ancient Egyptian hair styling and wig construction. The article describes wig construction and decoration in the period and a modern recreation of an ancient Egyptian wig.